Competitive Advantage Of Small And Medium Enterprises (SMEs) In Terms Of Entrepreneurial And Market Orientation - Udik Jatmiko (International Journal on Social Science, Economics and Art, 2022)
The problem that is the focus of this research is the marketing strategy of wood craft business actors in Tulungagung which is less effective in maintaining its competitive advantage in the business area when viewed from the aspect of entrepreneurial orientation, market orientation. Respondents in this study were business actors as many as 31 people who were used as samples. The analysis technique is carried out by descriptive analysis and inferential statistics through validity, reliability, multiple linear regression test, t test and F test. The results of this study indicate that the entrepreneurial orientation variable partially and significantly affects the competitive advantage of wood craft business actors in Tulungagung. Furthermore, market orientation variable partially has no effect on the competitive advantage of wood craft business actors in Tulungagung. Simultaneously entrepreneurial orientation and market orientation have a significant effect on the competitive advantage of wood craft business actors in Tulungagung. It is hoped that business actors will continue to focus their efforts on factors that can help in navigating competition with innovation and see market share so that they have a competitive advantage